Working from Home in Developing Countries - Charles Gottlieb; Jan Grobovsek; Markus Poschke; Fernando Saltiel (Institute of Labor Economics (IZA), 2020)
We examine workers' ability to work from home, as well as their propensity to actually work from home in developing countries. We use worker-level STEP data covering the task content of jobs to measure the ability to work from home. While the ability to WFH is low in developing countries, it exhibits significant heterogeneity across and within occupations and worker characteristics. Patterns of actual work from home in data from Brazil and Costa Rica align closely with those predicted based on STEP data, in terms of both overall levels and variation with occupation and individual characteristics.
Keywords: J21; J22; O1; 330; remote work; work from home; tasks; occupations; COVID-19